2004
DOI: 10.1086/424530
|View full text |Cite
|
Sign up to set email alerts
|

Germline PHOX2B Mutation in Hereditary Neuroblastoma

Abstract: Merlin-rapid analysis of dense genetic maps using sparse gene flow trees. Nat Genet 30:97-101 Cordell HJ (2004) Bias toward the null hypothesis in modelfree linkage analysis is highly dependent on the test statistic used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
182
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(191 citation statements)
references
References 30 publications
4
182
0
5
Order By: Relevance
“…Cases of familial neuroblastoma often present with multifocal or bilateral adrenal primary tumors and are diagnosed at a median of 9 months of age. Neuroblastoma also occurs in patients with neurocristopathies such as Hirschsprung disease and central hypoventilation syndrome (CHS), and although the underlying etiologies of these associations are not clear, mutations in the PHOX2B gene that are associated with Hirschsprung disease and central hypoventilation have also been detected in some cases of familial neuroblastoma [15][16][17]. Furthermore, although there have been a number of reported cases of neuroblastoma in patients with neurofibromatosis, the role of germline NF1 mutations in the etiology of neuroblastoma remains unclear [18].…”
Section: Epidemiology and Geneticsmentioning
confidence: 99%
“…Cases of familial neuroblastoma often present with multifocal or bilateral adrenal primary tumors and are diagnosed at a median of 9 months of age. Neuroblastoma also occurs in patients with neurocristopathies such as Hirschsprung disease and central hypoventilation syndrome (CHS), and although the underlying etiologies of these associations are not clear, mutations in the PHOX2B gene that are associated with Hirschsprung disease and central hypoventilation have also been detected in some cases of familial neuroblastoma [15][16][17]. Furthermore, although there have been a number of reported cases of neuroblastoma in patients with neurofibromatosis, the role of germline NF1 mutations in the etiology of neuroblastoma remains unclear [18].…”
Section: Epidemiology and Geneticsmentioning
confidence: 99%
“…[75][76][77][78]. These clinical observations suggested that a gene or genes implicated in the genesis of Hirschsprung disease or CCHS may confer a predisposition to develop NB (79,80). PHOX2B is a homeobox gene that is a master regulator of autonomic nervous system development.…”
Section: Inactivating Mutations In Phox2bmentioning
confidence: 99%
“…Patients with CCHS have a predisposition for developing tumors of the SNS, such as neuroblastoma, ganglioneuroma and ganglioneuroblastoma (43). Soon after the discovery of the role of PHOX2B in CCHS, four independent studies revealed heterozygous missense and frame-shift mutations in the PHOX2B gene, both in hereditary and sporadic neuroblastoma (44)(45)(46)(47). These mutations were rare in all four studies indicating locus heterogeneity for predisposition of inherited disease, but still demonstrated the importance of the PHOX2B gene in neuroblastoma oncogenesis and initiation (Fig.…”
Section: Neural Crest and Development Of The Sympathetic Nervous Systemmentioning
confidence: 99%